The Role of the Village Government in the Development of MSMEs in Torosiaje Village, Popayato District, Pohuwato Regency - Asni Asumbo; Roy Hasiru; Maya Novrita Dama; Melizubaida Mahmud; Ardiansyah Ardiansyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aimed to determine the Role of Village Government in developing UMKM and factors influencing the development of UMKM in Torosiaje Village, Popayato Subdistrict, Pohuwato Regency. The study used a descriptive method with qualitative research in which its data collection techniques used were observation, interviews, and documentation. Meanwhile, the data analysis was carried out through data reduction, data display, and conclusion drawing. The study findings indicated that the role Of government was crucial in the development of UMKM, where it ensured acces to capital, expanded market access, regulation,and digitalization. In addition UMKM also had several factors influencing their development, including internal, external.